Autophagy mediated by ROS-AKT-FoxO pathway is required for intestinal regeneration in echinoderms - Chuili Zeng; Ming Guo; Ke Xiao; Chenghua Li (Cell Communication and Signaling)
Abstract Autophagy is essential for maintaining material balance and energy circulation and plays a critical role as a regulatory mechanism in tissue regeneration. However, current studies primarily describe this phenotype, with limited exploration of its molecular mechanisms. In this study, we provided the first evidence that autophagy is required for intestinal regeneration in Apostichopus japonicus and identified a previously unrecognized regulatory mechanism involved in this process. We observed that autophagy activation was significantly associated with enhanced regeneration, and its upregulation was shown to be regulated by reactive oxygen species (ROS) bursts. Mechanistically, ROS induced the dephosphorylation of Forkhead box protein O (FoxO) through AjAKT dephosphorylation. The dephosphorylated AjFoxO translocated to the nucleus, where it bound to the promoters of AjLC3 and AjATG4, inducing their transcription. This study highlights the ROS-AjAKT-AjFoxO-AjATG4/AjLC3 pathway as a novel regulatory mechanism underlying autophagy-mediated intestinal regeneration in echinoderms, providing a reference for studying regenerative processes and cytological mechanisms in economically important echinoderms. Graphical Abstract Scheme depicting the necessity and molecular regulatory mechanisms of autophagy during the process of intestinal regeneration in A. japonicus.The activation of autophagy during intestinal regeneration is positively correlated with the accumulation of ROS, which induces the dephosphorylation of AjFoxO by mediating the dephosphorylation of AjAKT. The dephosphorylated AjFoxO then entered the nucleus, interacted with the promoters of AjATG4 and AjLC3, and regulated autophagy levels by mediating the transcription of autophagy-related genes AjATG4 and AjLC3, thereby regulating intestinal regeneration probably via ROS-AjAKT-AjFoxO-AjATG4/AjLC3 pathway. The figure was constructed by FigDraw ( www.figdraw.com/ID:rrPwA263e3 ).